Pelatihan Senam Aerobik untuk Meningkatkan Kebugaran Jasmani Secara Online - Andi Nurcahyo; Metta Christiana; Ahmad Muhaimin (Jurnal Pengabdian Olahraga Masyarakat, 2023)
ABSTRACTSport is exercise of the body as well as the movement of the legs and arms, by exercising every day the body will be healthy and fit, so with sports the people of Semarang City experience physical fitness. One of the sports that is currently popular with the public is Aerobic Gymnastics. Aerobic Gymnastics tends to be of interest to women. Women Community in the Mugasari, Semarang,  really want aerobic exercise, because of the covid-19 pandemic, aerobic exercise is done online. Aerobic Gymnastics Online is carried out in the Mugasari community, Central Semarang with Zoom. If the participants are not able to operate Zoom, then Zoom/Online Aerobic Gymnastics training is held. The results of the questionnaire of people who follow the most dominant are at the age of 50 years with a percentage of 25%. Then for aerobic exercise, it is also widely accepted in the community, it can be seen from the results of the questionnaire form with a percentage of 100 percent because aerobic exercise according to the results of the questionnaire form greatly improves physical fitness, and is useful in losing weight. As many as 15.4% of respondents experienced interference with aerobic exercise online with the average answer being a poor internet network. The results of the activity went smoothly. Not only women, even beyond expectations, men also participated in the training enthusiastically accompanied by enthusiasm through the Zoom application.ABSTRAKOlahraga adalah olah tubuh serta gerakan kaki dan tangan, dengan berolahraga setiap hari tubuh akan sehat dan bugar, maka dengan adanya olahraga masyarakat Kota Semarang mengalami kebugaran jasmani. Salah satu olahraga yang saat ini digemari masyarakat yaitu Senam Aerobik. Senam Aerobik diminati kaum wanita. Ibu- ibu di lingkungan Mugasari sangat menginginkan adanya senam aerobic, karena pandemic covid 19 maka senam aerobic dilakukan secara Daring Senam aerobik daring dilakukan oleh komunitas Mugasari Semarang melalui Zoom. Sebagian peserta tidak dapat mengoperasikan Zoom. Hasil kuesioner peserta senam aerobik daring, sebagian besar peserta yang mengikuti berusia 50 tahun yaitu sebanyak 25% peserta. Senam aerobik dapat diterima oleh 100% peserta karena dengan senam aerobik dapat meningkatkan kebugaran dan menurunkan berat badan. Sebanyak 15,4% peserta mengeluhkan buruknya kualitas internet yang digunakan. Kegiatan tersebut berjalan dengan lancar. Bukan hanya wanita yang menjadi peserta, namun juga para pria berpartisipasi dengan antusias. Kata kunci: Zoom, senam aerobik, online